The Impact of Travel 2.0 on Travelers Booking and Reservation Behaviors - Elçi, Alev; Abubakar, A. Mohammed; Ilkan, Mustafa; Eluwole, Kayode K.; Lasisi, Taiwo Temitope (SAGE Publications Ltd info@sagepub.co.uk, 2017)
The Internet offers a rich atmosphere for prospective travelers to gain familiarity, and harvest and retrieve travel-related information and resources. An increasing number of tourism and hospitality firms have turned their attention to new business opportunities on the Web. Travel 2.0 has emerged as a new tool for competitive advantage. This study draws on social cognitive theory and the DeLone and McLean Information Systems (D&M IS) success model to diagnose the impact of websites design quality on booking/reservation intentions from a travelers’ perspective. This research model was tested with 700 valid data collected from travelers using Travel 2.0 websites through online survey using SPSS v18 for the analysis. The results of the data analysis provided support for the hypothesized relationships of e-service and system quality with booking/reservation/purchase behavioral intention implying that an e-travel site’s quality is an essential success factor for tourism enterprises. However, information quality of an e-travel site is negatively related to booking/reservation intention. Cross-sectional design and self-report measures are the shortcomings of the study. Little research has been done on the relation between websites design (e-service, information, and system) quality, and booking/reservation intention. This article presents new insights into how these variables may influence potential tourist. © 2017, 2017 K.J. Somaiya Institute of Management Studies and Research.
Keywords: booking; purchase intention; reservation; Travel 2.0; Turkey